Bioactive Compounds and Antioxidant Properties of Mucus from Freshwater Snails Viviparus contectus and Planorbis rubrum - Kocabas, Filiz Kutluyer; Kocabas, Mehmet; Kizak, Volkan; Korkmaz, Busra; Benzer, Fulya; Erisir, Mine (Pleiades Publishing Inc, 2025)
As a viscous-elastic substance, snail mucus has a great attention in the medical and cosmetic industries in recent years due to contain many bioactive compounds. Freshwater snails are cosmopolite aquatic invertebrates and distribute nearly all types of inland aquatic bodies due to their adaptive abilities, rapid growth and short life cycles and, the compounds of mucus derived from freshwater snails has not been well documented. Hence, this study focused on identification bio-active ingredients and determination of protein content and antioxidant enzyme activities in freshwater snails Viviparus contectus and Planorbis rubrum mucus. Bioactive constituents of mucus in freshwater snails were characterized by Gas Chromatography-Mass Spectrometry (GC-FID-MS) analysis. Antioxidants (GSH, SOD, CAT and GSH-Px) and protein content were assessed in freshwater snails. Our data revealed that thirteen compounds are characterized with nonadecanoic acid methyl ester (11.57%), nonadecane (5.01%) and heptadecanoic acid methyl ester (4.19%) as the main components of P. rubrum mucus while eleven compounds are characterized with farnesol (11.23%), 5-hydroxymethyl-1,1,4 alpha-Trimethyl-6-methylene-decahydronphthalen-2-ol (9.73%), kaur-16-en-18-oic acid methyl ester (9.64%), tricosane (9.62%), and kaurene (8.44%) as the main components of V. contectus mucus. Nonadecanoic acid methyl ester and nonadecane, known as effective bioactive constituents having antimutagenic and antitumor capability, were determined with 11.57 and 5.01% of the total bio-active composition of P. rubrum mucus, respectively. As a major constituent, farnesol was detected with 11.23% of the total bio-active composition of V. contectus mucus. Moreover, the presence of kaurene, known as a potent bioactive compound for cancer treatment, in notably quantity in V. contectus mucus. In addition, GSH levels and SOD, CAT, and GPx activities was highest level in P. rubrum compared to V. contectus. Protein content was highest level in V. contectus than P. rubrum. Overall, individual compounds of V. contectus and P. rubrum mucus could be isolated and purified and used for the treatment of a variety of human ailments.
Keywords: Viviparus contectus; Planorbis rubrum; freshwater snail; mucus; antioxidants